Glycemic control and its influencing factors in type 2 diabetes patients in Anhui, China - Xing, Xiu-Ya; Wang, Xin-Yi; Fang, Xi; Xu, Jing-Qiao; Chen, Ye-Ji; Xu, Wei; Wang, Hua-Dong; Liu, Zhi-Rong; Tao, Sha-Sha (Frontiers in Public Health, 2022)
Objective To investigate the status of glycemic control and analyze its influencing factors in patients with type 2 diabetes (T2D) in Anhui, China. Methods Using a multi-stage random stratified sampling method, 1,715 T2D patients aged 18-75 years old were selected from 4 counties or districts in Anhui Province in 2018. Questionnaire survey, physical examination and fasting plasma glucose (FPG) test were performed on all patients. According to the 2010 American Diabetes Association criteria, FPG was used to evaluate the glycemic control status of patients, and FPG HbA1c (glycosylated hemoglobin) < 7.0% was defined as good glycemic control. The influencing factors of glycemic control rate were analyzed by multivariate unconditional logistic regression. Results The rate of T2D patients with good glycemic control in the Anhui Province was 22.97%. The results showed that female was a protective factor for glycemic control in T2D patients (OR=0.75, P=0.031) while low educational level when compared with junior high school and college and above (OR=2.69, P=0.001), rural (OR= 1.94, P=0.018), central obesity when compared with normal body type (OR = 1.55, P=0.002) duration of disease when over 10 years of illness versus less than 3 years (OR=2.70, P<0.001), were risk factors. Conclusions The rate of T2D patients with good glycemic control in Anhui Province is relatively low, and the publicity and education on the importance of glycemic control should be further strengthened in T2D patients, and targeted intervention measures should be carried out for risk groups.